ANALISIS MODEL PREDIKSI KEBANGKRUTAN PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BEI 2015-2017 - Tri Nurdyastuti; Dibyo Iskandar (Jurnal Bisnis Terapan, 2019)
The purpose of study was to test the difference method of altman, method of springate, method of zmijewski and method of grover in predicting bankruptcy on food and beverages companies listed on the indonesia stock exchange period 2015-2017. Hypothesis test using the test tool is one way anova, one way anova kruskal-wallis, mann-whitney test and calculation the level of accuracy predicting method. The test result showed there was a significant difference between method of altman, method of springate, method of zmijewski and method of grovern predicting bankruptcy on food and beverages companies listed on the Indonesia stock exchange period 2015-2017. Grover method has a higher degree of accuracy than method of altman, method of springate, and method of zmijewski, so it is better make use of predicting bankruptcy in food and beverages companies listed on the indonesia stock exchange period 2015-2017..